REVITALISING PUBLIC POLICY TO SUPPORT GOOD AND CLEAN GOVERNANCE - Riza Arizany Azahra; Iman Hikmat Nugraha (INTERNATIONAL JOURNAL OF FINANCIAL ECONOMICS, 2024)
Revitalising public policy is an integral effort to support the creation of good and clean governance. This process includes improving the capacity of human resources, adopting modern technology, and strengthening the regulatory framework to increase transparency and accountability in government. In addition, close collaboration between various government agencies and active participation from the public are essential to ensure the successful implementation of policies that are more effective and responsive to public needs. With this revitalisation, it is hoped that a more efficient government, free from corrupt practices, and able to provide maximum services to the community, will support sustainable and inclusive development.